The upper-level atmospheric pathway of ENSO’s impact on winter rainfall in southern China - Jiawen Zhang; Kaiming Hu; Gang Huang; Ya Wang (Geoscience Letters)
Abstract Using observational and reanalysis datasets from 1979 to 2023, this study investigates the role of upper- and middle-tropospheric circulation anomalies in mediating the influence of El Niño-Southern Oscillation (ENSO) on South China winter precipitation (SCWP). The results show that El Niño events trigger a prominent quasi-barotropic cyclonic anomaly over East Asia, with peak intensity occurring between 150 and 200-hPa in the upper troposphere. Eastward of this anomaly, mid-tropospheric southerly wind anomalies induce warm air advection along the East Asian coastline, which enhances vertical upward motion. Additionally, the differential vertical vorticity advection—driven by stronger vorticity anomalies and amplified zonal winds in the upper troposphere compared to the lower levels—further intensifies the ascending motion along the eastern flank of the cyclonic anomaly. Consequently, this upper- and middle-tropospheric anomalous cyclone creates a corridor of ascending motion that extends from southern China to the region south of Japan, leading to the development of positive precipitation anomalies in the region. This finding could help improve the seasonal forecast skill of SCWP.